Festa de São Sebastião em Cachoeira do Arari: uma perspectiva geográfica da religiosidade do caboclo marajoara - AVELAR, Gabriel Augusto Pacheco de (2023)
Through religiousness, humans express their beliefs, doctrines, feelings, teachings, devotions, and/or dogmas, becoming the main vehicle of cultural and ideological manifestations of a great part of the population. Intending to recognize the memory of the cultural and historical preservation of the population, geography seeks to study religious manifestations, trying to understand the reasons why humans attribute meanings to places in the geographical space as sacred. This work will contribute to understanding the importance of religiousness in the culture of the Marajoara people, as well as their beliefs and customs, which are legacies of the colonization of the Amazon. Therefore, the objective was to carry out a literature review on the manifestation of the religiousness of the Marajoara people in the Amazon region, especially in the festival of Saint Sebastian in Cachoeira do Arari. Specifically, we sought to investigate the role of geography in understanding the manifestation of religiousness; analyze the meaning of the festival of Saint Sebastian for the Marajoara people; identify and understand the local customs related to the manifestation of Marajoara religiousness; and finally, emphasize the importance of the historical and cultural preservation of the festival of Saint Sebastian. For this discussion, we opted for a literature review of an exploratory nature, of a qualitative approach. The aim is to analyze bibliographical sources such as scientific articles, books, theses, and dissertations. In addition to direct observation of the customs of the Marajoara people in the Amazon region. Based on the results presented, it is concluded that religiousness is an important element in the identity of Amazonian culture and that the Festival of Saint Sebastian in Cachoeira do Arari is one of the greatest religious and cultural events of the region. Therefore, it is essential to preserve the religiousness and culture of these places, since they are essential elements for the identity of the Amazon region and for understanding the history and culture of these people. In addition, the preservation and sharing of the history and culture of these places, through cultural tourism, offers economic and social benefits to the region, in addition to offering the opportunity for ancestral rituals to be preserved.